Accounting System Software Based On Microsoft Access At Mie Pangsit Harum - Yessica Stephanie Lim; Muhammad Taufik (Universitas Internasional Batam, 2023)
Due to the lack of an accounting recording system at Mie Pangsit Harum Company, transactions are recorded manually. Therefore, inefficiencies and risks are associated with the accuracy and completeness of the reports required for making decisions. This community service aims to build an accounting system using Microsoft Access that scopes include form, bookkeeping system, and financial reporting. The data collection methodology was obtained from interviews and technical observations with partners. The output of bookkeeping software includes account list and ledger. Moreover, transactions output includes general journal form, purchase form, and sales form. After bookkeeping, we generate system around financial report such as statement of profit or loss, statement of financial position, statement of cash disbursement, purchase report, and sales report. The output would guide SMEs in knowing financial conditions for making better decision to increase their sales and controlling expenses.